2016
DOI: 10.1016/j.ces.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic solvent extraction of rare earth elements from a mixed oxide concentrate leach solution using Cyanex® 572

Abstract: Solvent extraction of rare earth elements (REEs) involves hundreds of individual extraction and phase separation cycles, fine adjustment of solution conditions, and individual stage and overall process times that are long. Therefore, we investigated microfluidic solvent extraction (microSX) of REEs from a leached mixed rare earth oxide (REO) mineral concentrate using a phosphorus-based cationic exchange extractant (Cyanex® 572). A Y-Y microchip was used, in which the aqueous and organic phases were contacted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…[21] As such, this technology has been used in numerous solvent extraction studies on metal extractions and separations. [22][23][24][25][26] A popular flow pattern is slug flow (also referred to as plug flow or Taylor flow) where the immiscible phases form a segmented flow of sequential slugs and plugs. Internal vortices are formed inside the plugs due to a shear exerted by the continuous phase on the surface of the plug, leading to a very efficient mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[21] As such, this technology has been used in numerous solvent extraction studies on metal extractions and separations. [22][23][24][25][26] A popular flow pattern is slug flow (also referred to as plug flow or Taylor flow) where the immiscible phases form a segmented flow of sequential slugs and plugs. Internal vortices are formed inside the plugs due to a shear exerted by the continuous phase on the surface of the plug, leading to a very efficient mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical impurity removal method is commonly used to remove impurities due to its convenience and low cost (Zhang et al, 2016;Zhou et al, 2017;Hamza et al, 2019). Some research has been done in this area, and it has been found that ammonia, ammonium bicarbonate, and sodium sulfide can be used for the removal of impurities (Li and Chi, 1997;Kolar et al, 2016;Zhou et al, 2017). According to these studies, flocs, whose main component is aluminum hydroxide, will be formed in the impurity removal process (Luo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…REEs (rare-earth elements) are known as the “treasure house of industrial materials” and fairly abundant in the earth’s crust, but the separation and purification of REEs are thorny issues since their physical and chemical properties are nearly identical. , To tackle this challenge, liquid–liquid solvent extraction is the commonly used technology in industrial production, and the increasing demand of security of industrial solvent extraction has become the central focus of scientific research . Currently, microreactors are widely studied in the field of liquid–liquid solvent extraction of rare-earth elements because extracting REEs in microreactors present many attractive properties: (1) Significant increase in boundary area and enhanced mass transfer; (2) low capital and operating costs, low energy consumption, and increase in efficiency of analytical techniques; (3) significantly improved and safer working environment and avoidance of emulsification. , Although the inability to deal with fluid containing solids is the limitation of microreactors, advantages could be obtained by using microfluidic extraction technology in the REEs separation process …”
Section: Introductionmentioning
confidence: 99%